Nickel-chromium (Ni–Cr) coatings deposited by magnetron sputtering for accident tolerant nuclear fuel claddings; Surface and Coatings Technology; Vol. 369 - Sidelev D. V. Dmitry Vladimirovich; Kashkarov E. B. Egor Borisovich; Syrtanov M. S. Maksim Sergeevich; Krivobokov V. P. Valery Pavlovich (2019, 2019)
Title screen